Moving across the border: modeling migratory bat populations. Issue 9 (27th September 2013) - Wiederholt, Ruscena; López-Hoffman, Laura; Cline, Jon; Medellín, Rodrigo A.; Cryan, Paul; Russell, Amy; McCracken, Gary; Diffendorfer, Jay; Semmens, Darius
Abstract : The migration of animals across long distances and between multiple habitats presents a major challenge for conservation. For the migratory Mexican free‐tailed bat ( Tadarida brasiliensis mexicana ), these challenges include identifying and protecting migratory routes and critical roosts in two countries, the United States and Mexico. Knowledge and conservation of bat migratory routes is critical in the face of increasing threats from climate change and wind turbines that might decrease migratory survival. We employ a new modeling approach for bat migration, network modeling, to simulate migratory routes between winter habitat in southern Mexico and summer breeding habitat in northern Mexico and the southwestern United States. We use the model to identify key migratory routes and the roosts of greatest conservation value to the overall population. We measure roost importance by the degree to which the overall bat population declined when the roost was removed from the model. The major migratory routes—those with the greatest number of migrants—were between winter habitat in southern Mexico and summer breeding roosts in Texas and the northern Mexican states of Sonora and Nuevo Leon. The summer breeding roosts in Texas, Sonora, and Nuevo Leon were the most important for maintaining population numbers and network structure – these are also the largest roosts. This modeling approach contributes to conservation efforts by identifying the most influential areas for bat populations, and can be used to as a tool to improve our understanding of bat migration for other species. We anticipate this approach will help direct coordination of habitat protection across borders.